Apuntes para el estudio de la religión maya de finales del siglo xvi - Caroline Cunill (Journal de la Société des Américanistes)
Notes about the study of Maya religion at the end of the 16th century. Indian witnesses and notaries’ participation in the idolatry processes contained in the yucatecan religious’ relaciones de méritos of the 16th century favored the transcription of many words in autochthonous language in the testimonies. We consider that this characteristic brings legitimacy to those sources that enlighten our comprehension of Colonial Maya religion’s contents and senses, as well as the mechanisms by which prehispanic rites were transmitted in the new society, despite adverse conditions to their reproduction.